Jonah the whale - Shreve Susan 1939-; Susan Shreve (New York : Scholastic, 1999)
After moving to a new town, Jonah, an eleven-year-old with a big imagination, reinvents himself as a talk show host, hoping this will somehow bring his absent father back.
M
740
M